Análise de desempenho das saídas de emergência por meio de simulações computacionais: o caso de projetos de edifícios universitários - Montenegro, Mariana Lima Oliveira (2016)
The fire safety parameters in Brazil are driven by prescriptive standards, which function as a basis for architects, whose design aim to the enforcement of such for a subsequent approval from the inspection authorities. The legislation needs to be in a constant review and evaluation. From this statement, the main goal of this work is to identify, in university building projects, potential gaps in the normative prescriptions about fire evacuation which raise intervention and correction proposals to their better effectiveness. The question to be answered at the end of the research is that there are differences and confluences solutions between prescriptive rules on emergency evacuation used in Rio Grande do Norte, when compared to the results obtained through computer simulations. For such, a gathering of information was initially held through a research in literature and documents concerning the matter. Later, based on established criteria, computer simulations were carried out to analyze the normative prescriptions applied to the chosen buildings. The simulations were performed by two software: PATHFINDER® (2014), related to the escape time and to the movement of the people while on the run; and DEPTHMAP® (2004), concerned the study of the spatial setting and its relation to the movement of the users in the buildings, according to the Space Syntax Theory (SS). From the analyzes results, prescriptive codes gaps were identified, such as regarding the design of the stairs, the maximum number of occupants and the maximum distance to safety; and effective points, as the need of enclosed stairs to decrease the maximum exhaust time. With the findings, gave subsidies to discuss the existing parameters and others that are not yet covered by SCI regulations, and the studied buildings design solutions. It is expected that the work will contribute to future research that deals the addressed issues or aimed at further the study here started.